Digital Narratives: The Evolution of Storytelling Techniques in the Age of Social Media - Harahap, Tinur Rahmawati; Nasution, Bincar; Nasution, Fauziah; Harahap, Adek Nilasari (PT Inovasi Pratama Internasional, 2024)
This article discusses the evolution of storytelling techniques in the era of social media through the approach of digital storytelling. Digital storytelling is a method of conveying narratives that combines elements of images, text, audio, and video to create a more engaging storytelling experience. This research indicates that digital storytelling can enhance the literacy skills of the younger generation in Indonesia, which faces challenges related to low reading interest. With advancements in information technology and widespread internet access, digital platforms such as vlogs and podcasts can be utilized to introduce stories to young audiences. The research methodology employed is a literature review, gathering data from various relevant sources. The findings suggest that digital storytelling is effective in increasing literacy interest among the younger generation and has the potential to serve as an innovative educational tool. This article aims to provide a deeper understanding of the evolution of digital storytelling within the context of contemporary social media.